Physical and mechanical characteristics evaluation of weakened endodontically treated teeth restored with fiber-reinforced composite: open apex and flared root canals - Alshetiwi, Dawood Salman Dawood (2023)
Endodontically treated teeth (ETT) with compromised root canals due to pervasive damage induced by root canal over-instrumentation and incomplete physiological root formation are at high risk of fracture. The use of intra-radicular posts in these teeth is accompanied by a large resin cement layer due to the discrepency in the size and shape between the post and root canal. This study was conducted to assess the combination of different forms of Fiber-reinforced composites (FRC) used to enhance mechanical behavior of compromised ETT. Eighty extracted human premolar teeth were used in this study. Teeth were randomly allocated to five experimental groups with sixteen teeth per group (n = 16). Eight teeth from each group (n = 8) were submitted for objectives 1-3. The remaining eight teeth (n = 8) were prepared for objective 4. Groups were divided according to canal preparation methods and intra-radicular restoration with either a standard prefabricated fiber post or anatomically customized relined fiber post. Samples were then submitted for evaluation of intracanal adaptation using polyvinyl siloxane (PVS) light body impression material and artificial aging using computer-controlled chewing simulator. Fracture resistance and push-out bond strength tests were then carried out through a universal testing machine followed by mode of failure analysis via a stereomicrosope and scanning electron microscope. Assessment of intra-canal adaptation showed a statistically significant difference (p<0.05) in PVS material weight between the groups. Group 1 (control) had the lightest weight of PVS material, followed by groups restored with customized fiber posts (Group 4 and Group 5) and groups restored with standard fiber posts (Group 2 and Group 3). Artificial aging test results through Pairwise Log-Rank comparisons revealed that there was no statistically significant difference between Group 1 (control group), Group 5 and Group 4 (p>0.05). Group 2 and Group 3 showed a statistically significant lower survival rate compared to all other groups. Results of fracture resistance test showed the highest fracture resistance (1796 N) in Group 5, and it was significantly higher compared to other groups (p<0.05), while Group 2 showed the lowest mean fracture resistance (758 N) and was significantly lower compared to the other groups. In relation to push-out bond strength test, Group 5 and Group 4 demonstrated a significantly higher bond strength at all root thirds (p<0.05) than Group 3, Group 2, and Group 1. The most frequently observed failure occurred between the resin cement and radicular dentin for all the groups. In conclusion, the use of short fiber-reinforced composite (SFRC) to reline the prefabricated FRC post has been proven to improve intracanal adaptation and result in higher survival rate, superior fracture resistance with favorable failure patterns and increased push-out bond strength values compared to standard prefabricated FRC posts.